Catching the waves: Following the leading edge of elongating RNA polymerase II - Henriques, Telmo (2013)
By precisely tracking the waves of elongating RNA polymerase II (Pol II) during gene activation, Danko et al. (2013) discovered a surprising diversity of elongation rates among and along human genes.